Embrace the path to better health / Emily Jothee Mathai - Mathai, Emily Jothee (Academy of Language Studies, 2024)
Our forefathers have left us with a great wealth of health proverbs such as Health is Wealth, The greatest wealth is health, and Good health is above wealth. These popular health related proverbs, which l noticed are connected to wealth, highlight the crucial roles both health and wealth play in leading a quality life. They reflect the understanding that health and wealth are fundamental to a fulfilling and prosperous life. Today, in our day-to-day life, we are extremely busy working for money, in the pursuit of earning, we often experience symptoms of fatigue, pain, stress, and illness, or we neglect the need for rest, proper nutrition, and exercise, in the long run, this takes a toll on our health, causing suffering and damage. Truly, we fail to listen to our own body's signals, leading to negative consequences for both our physical and mental well-being.